Profile of the senior caregiver in situation of pandemic for SARS-COV-2, Lima-Peru - Navarrete-Mejía, Pedro Javier (2020)
Objetive: To know the profile of the older adult caregiver in a SARS-COV-2 pandemic, Lima-Peru. Materials and methods: observational and cross-sectional study; population made up of 92 caregivers of older adults, non-relatives and who receive remuneration, both sexes, over 18 years of age, voluntary participation; older adults residing in districts of northern Lima, economic stratum C and D. Sociodemographic variables, education / training, vaccines, self-confidence or self-safety, and degree of anxiety or stress were evaluated in the caregiver; the older adult variables included were sociodemographic, vaccines, disabilities and disease. Questionnaire was completed virtually during the last week of March 2020. Results: caregiver profile, mean age 33.48 years, 95.7% female, 77.2% do not have training in hand washing, 96.7% without training in stress management in older adults. Self-confidence or self-confidence in caring for the elderly was 1.97 (scale from 0 to 5) and the degree of anxiety or stress during care 8.03 (scale from 0 to 10). Conclusions: deficiencies in the profile of the caregiver who oversees the elderly are evident, the development of strategies to reverse the problem is urgent, the prioritization of actions for the care of the elderly as a vulnerable person are urgent. Strategies should include caregiver training, stress self-management, and access to home care services, among others.